1999
DOI: 10.1042/bj3440331
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression and characterization of YSA1H, a human adenosine 5′-diphosphosugar pyrophosphatase possessing a MutT motif

Abstract: The human homologue of the Saccharomyces cere isiae YSA1 protein, YSA1H, has been expressed as a thioredoxin fusion protein in Escherichia coli. It is an ADP-sugar pyrophosphatase with similar activities towards ADP-ribose and ADP-mannose. Its activities with ADP-glucose and diadenosine diphosphate were 56 % and 20 % of that with ADP-ribose respectively, whereas its activity towards other nucleoside 5h-diphosphosugars was typically 2-10 %. cADP-ribose was not a substrate. The products of ADP-ribose hydrolysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 28 publications
2
21
1
Order By: Relevance
“…In terms of apparent K m , the affinity of AGPPase for NAD ϩ , ADPribose, UDPG, and CDPglucose is about 4-to 5-fold lower than that for ADPG. In contrast to the case of nucleoside diphosphate sugar pyrophosphatases occurring in animals, yeast, and bacteria (16)(17)(18)(19)(20)(21), AGPPase exhibits a high affinity to the synthetic substrate bis-PNPP, which is a reagent commonly used to measure phosphodiesterase activities (10).…”
Section: Verification Of Reaction Products and Enzyme Designationmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of apparent K m , the affinity of AGPPase for NAD ϩ , ADPribose, UDPG, and CDPglucose is about 4-to 5-fold lower than that for ADPG. In contrast to the case of nucleoside diphosphate sugar pyrophosphatases occurring in animals, yeast, and bacteria (16)(17)(18)(19)(20)(21), AGPPase exhibits a high affinity to the synthetic substrate bis-PNPP, which is a reagent commonly used to measure phosphodiesterase activities (10).…”
Section: Verification Of Reaction Products and Enzyme Designationmentioning
confidence: 99%
“…Remarkably, the enzyme is not affected by typical phosphodiesterase and nucleoside diphosphate sugar pyrophosphatase effectors such as metal ions, fluoride, metal-binding reagents, sulfhydrylgroup reacting agents, and reducing compounds (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Also, in clear contrast to phosphodiesterases and nucleotide sugar hydrolases having basic optimum pH (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), AGPPase shows a sharp pH-activity profile with optimal activity occurring at pH 6.0, which dramatically decreases at basic pH values (Fig. 1).…”
Section: Verification Of Reaction Products and Enzyme Designationmentioning
confidence: 99%
See 1 more Smart Citation
“…NUDT5 may also prevent transcriptional errors and mistranslation. Prior studies (19)(20)(21) also found that lowered NUDT5 expression led to cell cycle inhibition in HeLa cells (21). Further studies indicated that the NUDT5 protein may have notable roles in regulating the G1-S transition in mammalian cells (22)(23)(24).…”
Section: Nudt5 Nudt9p1 Nudt16 Nudt17 --------------------------------mentioning
confidence: 99%
“…ADP Ribose is a member of a family of proteins involved in a number of cellular processes such as DNA repair, genomic stability and programmed cell death (19,20). In experiments in vitro, NUDT5 suppressed the increased mutation rate of cancer cells and may act in concert with NUDT1 or NUDT15 in antimutagenesis (19,20).…”
Section: Nudt5 Nudt9p1 Nudt16 Nudt17 --------------------------------mentioning
confidence: 99%